2017
DOI: 10.20473/jbk.v5i1.2016.27-34
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Keinginan Pasangan Usia Subur (Pus) dalam Penggunaan Metode Kontrasepsi Jangka Panjang

Abstract: One of the most eff ective eff ort in the family planning program was to control fertilitas and press the population growth rate was used contraception. In the area of Puskesmas Pacar Keling Surabaya interest of acceptor which used short term contraceptive method still high than long term contraceptive method. This research used analytical observational study with case control methods. The population is all woman reproductive age couples aged 15-49 years old in the area of Puskesmas Pacar Keling Surabaya. Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
0
4
0
6
Order By: Relevance
“…The same idea was also stated by Sumartini in her research on the affecting factors of the low interest in using tubal ligation contraception method of among women. The result of the study concluded that there was a significant relationship between motivation, knowledge, support of husband with the child bearing age women interest in using tubal ligation contraception method (Sumartini, 2016).…”
Section: The Relation Of Husband's Support and Low Interest Of Tubal mentioning
confidence: 94%
“…The same idea was also stated by Sumartini in her research on the affecting factors of the low interest in using tubal ligation contraception method of among women. The result of the study concluded that there was a significant relationship between motivation, knowledge, support of husband with the child bearing age women interest in using tubal ligation contraception method (Sumartini, 2016).…”
Section: The Relation Of Husband's Support and Low Interest Of Tubal mentioning
confidence: 94%
“…Support from the husband is very important in choosing the contraceptive method to use. Women will have more confidence in using contraception when they are supported by their husbands [19]. Support from the husband can also be seen while attending the family planning counselling, by following the husband's family planning counselling that has a positive impact on the wife.…”
Section: The Relationship Between Husband's Support and Selection Of mentioning
confidence: 99%
“…Kemudian pengetahuan, dan edukasi yang kurang terkait MKJP, dukungan pria/suami, serta mahalnya biaya juga mendorong responden dalam tidak menggunakan kontrasepsi jangka panjang (Ane, 2020;Rosmawaty, 2017). Penelitian selanjutnya ditemukan 62% responden yang mengalami efek samping memutuskan untuk berhenti menggunakan KB jangka panjang (Septalia & Puspitasari, 2016;Sumartini & Indriani, 2016).…”
Section: Distribusi Jenis Alat Kontrasepsi Yang Digunakanunclassified